Effectiveness of Pre-Procedural Antimicrobial Mouthwash Rinse with a Simple Water Rinse on the Dry Socket after Third Molar Extractions (Medical Forum Monthly, 2021)
Objective: To compare the effectiveness of pre-procedural antimicrobial mouthwash rinse with a simple water rinse on the dry socket after third molar extractions at a tertiary care hospital, Karachi.Study Design: A Randomized Control Trial StudyPlace and Duration of Study: This study was conducted at the Oral and Maxillofacial Surgery Department, Liaquat College of Medicine and Dentistry, Darul-Sehat Hospital, Karachi from October 2019 to April 2020.Materials and Methods: A total of 140 patients were selected who fulfilled the inclusion criteria and divided in two groups, (n=70) in controlled and (n=70) in experimental group. Both groups underwent the extractions of mesioangular impaction of Mandibular third Molars on either side under local anesthesia. Pre-procedural antimicrobial mouth rinsing was done only in experimental group. Presence of dry socket was assessed on follow up (third post op day) by scoring intensity of pain on VAS and presence of exposed bone clinically.Data had been analyzed using SPSS version 17.0. Mean and standard deviation will be calculated for age. Frequency and percentages will be calculated for gender, effectiveness in both groups. Chi-square test will be applied to compare the effectiveness in both groups.Results: The mean age was 34 years with standard deviation of + 9 years. In control group 39 were female compared with 45 subjects females in preprocedural antimicrobial mouth rinsing group. Chi-square test showed the significant difference for VAS between groups (p<0.001) and also significant difference for exposed bone (p = 0.018).Conclusion: We concluded that the use of preprocedural antimicrobial mouth rinsing with chlorhexidine mouthwash before the extractions of mandibular third molars seems to be an appropriate option for the reduction of alveolitis.